IMPLEMENTASI MODEL DESAIN PEMBELAJARAN ASSURE BERBASIS MULTIMEDIA DALAM MENGATASI KESULITAN BELAJAR FIQH DI MI AT-TAQWA MADIUN - Han Sein, Lau; Abdul Azis; Nurul Atik Hamida; Siti Khulasoh; Muchdjabir Wahid; Andy Litehua (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the implementation of the ASSURE instructional design model (Analyze Learners, State Objectives, Select Methods, Media, and Materials, Utilize Media and Materials, Require Learner Participation, Evaluate and Revise) integrated with multimedia to overcome student learning difficulties in Fiqh. The research was conducted at MI At-Taqwa Madiun. Using a qualitative approach and a descriptive method, data was collected through direct observation, in-depth interviews, and document analysis. The findings indicate that the application of the multimedia-based ASSURE model is an effective strategy. The process begins with an analysis of student characteristics and learning styles, followed by the selection of relevant methods, media, and teaching materials. The success of this model is also supported by active student participation, which has been shown to minimize their learning difficulties. In conclusion, the ASSURE model, enriched with multimedia, serves as a significant alternative solution to improve the quality of Fiqh learning.